A Study of the Regulatory Mechanism of the CB1/PPARγ2/PLIN1/HSL Pathway for Fat Metabolism in Cattle - Liu, Ruili; Liu, Xianxun; Bai, Xuejin; Xiao, Chaozhu; Dong, Yajuan (Frontiers in Genetics, 2021)
Fat metabolism is closely related to the economic characteristics of beef cattle. Therefore, regulating fat deposition and increasing intramuscular fat deposition are among the main goals of breeders.In this study, we aim to explore the regulatory role of CB1 gene on PPARγ2/PLIN1/HSL pathway in fat metabolism, and to further explore the differential expression of regulatory factors of this pathway in Shandong black cattle and Luxi cattle. In this study, CB1 overexpression stimulated lipid synthesis in adipocytes to some extent by increasing the levels of FASN and ACSL1. CB1 inhibitors reduced the lipid content in adipocytes, and the expression of GLUT1 and Insig1 was decreased. In addition, overexpression of CB1 decreased the expression of PPARγ2 and led to an increase in PLIN1 expression and a decrease in HSL expression in adipocytes. We also found that the CB1/PPARγ2/PLIN1/HSL was differentially expressed in the different breeds of cattle and was involved in the regulation of fat metabolism, which affected the fatty acid content in the longissimus dorsi muscle of the two breeds. In conclusion, CB1 participated in lipid metabolism through PPARγ2 and PLIN1 mediated regulation of HSL, and improves lipid formation in adipocytes. In conclusion, CB1/PPARγ2/PLIN1/HSL pathway may be involved in the regulation of lipid metabolism.